The Effect of Workplace Envy, Negative Emotion, and Perception of Injustice on Turnover Intention: Conceptual Framework - Dahri, Nur Wahyunianti; Aqil, Muhammad (SMARTINDO, 2024)
Purpose - This study examines the effect of workplace envy, negative emotions, and perceptions of injustice on turnover intention. Design/methodology/approach – This paper explored the article published in various databases. Originality - This study will develop the variable of negative behavior that is detrimental to the organization because several studies have found that the number of negative behaviors of employees in organizations is increasing globally. Findings and Discussion - Three propositions developed in this study relate to empirical and theoretical issues: first, workplace envy has a positive and significant effect on turnover intention; second, negative emotion has a positive and significant effect on turnover intention; and third, the perception of injustice has a positive and significant effect on turnover intention. Conclusion – The discussion is carried out as a literature review of previous studies in developing propositions. This research aims to contribute to the literature and conceptual model of the influence of work motivation and transformational leadership on employee performance, with job satisfaction as a mediating variable. Methodology - This type of research is quantitative research with a survey method. In the census method, because the entire population is used as a sample, the data collection method used is a questionnaire.